2017
DOI: 10.1089/wound.2016.0714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traumatic Lower Extremity Injuries Beyond Acute Care: Movement-Based Considerations for Resultant Longer Term Secondary Health Conditions

Abstract: Significance: Advances in field-based trauma care, surgical techniques, and protective equipment have collectively facilitated the survival of a historically large number of service members (SMs) following combat trauma, although many sustained significant composite tissue injuries to the extremities, including limb loss (LL) and limb salvage (LS). Beyond the acute surgical and rehabilitative efforts that focus primarily on wound care and restoring mobility, traumatic LL and LS are associated with several debi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 99 publications
1
21
0
Order By: Relevance
“…Including subjects followed for a longer time would allow more time for behavioral and health changes that may take place after the injury to affect the incidence of common chronic diseases, in particular. As mentioned earlier, previous prospective studies in occupational and nonoccupational populations have found that injuries may reduce physical activity and be associated with subsequent weight gain . We did still observe modest increases in HRs for chronic diseases, and the increase in mortality for circulatory disease among men was statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…Including subjects followed for a longer time would allow more time for behavioral and health changes that may take place after the injury to affect the incidence of common chronic diseases, in particular. As mentioned earlier, previous prospective studies in occupational and nonoccupational populations have found that injuries may reduce physical activity and be associated with subsequent weight gain . We did still observe modest increases in HRs for chronic diseases, and the increase in mortality for circulatory disease among men was statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…Nerve injuries are more prevalent than amputation in trauma patients, and a large majority of nerve injuries result in chronic pain. 63 Whereas amputations represented just over 3% of the 52,351 reported casualties across all services from 2001–2015, 2 up to 24–53% of Service members injured in OIF/OEF had extremity pain. 64,65 Because trauma and subsequent amputation result in nerve injuries similar to those in non-amputee nerve trauma patients, data from the successful use of percutaneous PNS in amputees suggest this therapy has the potential to provide significant pain relief and restoration of function following other types of injuries or trauma (both combat- and noncombat-related) that have a high prevalence among military Service members and Veterans.…”
Section: Percutaneous Pns Has Potential Applications In Post-surgicalmentioning
confidence: 99%
“…Over 50,000 US Service members have been injured in military conflicts since 2001 (e.g., Operation Enduring Freedom [OEF], Operation Iraqi Freedom [OIF]), and as a result, over 1,600 major limb amputations have occurred. 1,2 Due to advances in military medicine including improved body armor, faster access to advanced life support and theater-based medical facilities, and effective technological care in the field, the mortality rate of severely injured Service members is decreasing. 3,4 As a result, there is an increasing prevalence of warriors surviving traumatic injuries and a strong emphasis on alleviating pain and improving quality of life in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Stepping strategies may be adapted that deviate from a symmetric pattern in order to prevent or minimize pain at the residual limb, socket interface, low back or intact knee (due to gait deviations). Although stability and comfort obtained through asymmetric gait may be critical for individuals with TFA during walking, 9,32 it is important to note that secondary health concerns (i.e., knee osteoarthritis and low back pain) 33 may arise from gait asymmetries and compensatory actions of the intact and residual limbs. Therefore, clinicians must consider multiple factors when determining appropriate rehabilitation goals.…”
Section: Cohortmentioning
confidence: 99%